Using internal strain and mass to modulate Dy⋯Dy coupling and relaxation of magnetization in heterobimetallic metallofullerenes DyM2N@C80 and Dy2MN@C80 (M = Sc, Y, La, Lu). Issue 2 (29th November 2022) - Hao, Yajuan; Velkos, Georgios; Schiemenz, Sandra; Rosenkranz, Marco; Wang, Yaofeng; Büchner, Bernd; Avdoshenko, Stanislav M.; Popov, Alexey A.; Liu, Fupin
Abstract : Relaxation of magnetization in DyM2 N@C80 and Dy2 MN@C80 (M = Sc, Y, La, Lu) series correlates, respectively, with the mass and size of the diamagnetic metal M. Abstract : Endohedral clusters inside metallofullerenes experience considerable inner strain when the size of the hosting cage is comparably small. This strain can be tuned in mixed-metal metallofullerenes by combining metals of different sizes. Here we demonstrate that the internal strain and mass can be used as variables to control Dy⋯Dy coupling and relaxation of magnetization in Dy-metallofullerenes. Mixed-metal nitride clusterfullerenes Dy x Y3− x N@ I h -C80 ( x = 0–3) and Dy2 LaN@ I h -C80 combining Dy with diamagnetic rare-earth elements, Y and La, were synthesized and characterized by single-crystal X-ray diffraction, SQUID magnetometry, ab initio calculations, and spectroscopic techniques. Dy x Y3− x N clusters showed a planar structure, but the slightly larger size of Dy 3+ in comparison with that of Y 3+ resulted in increased elongation of the nitrogen thermal ellipsoid, showing enhancement of the out-of-plane vibrational amplitude. When Dy was combined with larger La, the Dy2 LaN cluster appeared strongly pyramidal with the distance between two nitrogen sites of 1.15(1) Å, whereas DyLa2 N@C80 could not be obtained in a separable yield. Magnetic studies revealed that the relaxation of magnetization and blocking temperature of magnetization in the DyM2 N@C80 series (M = Sc, Y, Lu) correlated with the mass of M, with DySc2 N@C80 showing the fastest and DyLu2 N@C80 the slowest relaxation. Ab initio calculations predicted very similar g -tensors for Dy 3+ ground state pseudospin in all studied DyM2 N@C80 molecules, suggesting that the variation in relaxation is caused by different vibrational spectra of these compounds. In the Dy2 MN@C80 series (M = Sc, Y, La, Lu), the magnetic and hysteretic behavior was found to correlate with Dy⋯Dy coupling, which in turn appears to depend on the size of M 3+ . Across the Dy2 MN@C80 series, the energy difference between ferromagnetic and antiferromagnetic states changes from 5.6 cm −1 in Dy2 ScN@C80 to 3.0 cm −1 in Dy2 LuN@C80, 1.0 cm −1 in Dy2 YN@C80, and −0.8 cm −1 in Dy2 LaN@C80 . The coupling of Dy ions suppresses the zero-field quantum tunnelling of magnetization but opens new relaxation channels, making the relaxation rate dependent on the coupling strengths. DyY2 N@C80 and Dy2 YN@C80 were found to be non-luminescent, while the luminescence reported for DyY2 N@C80 was caused by traces of Y3 N@C80 and Y2 ScN@C80 .